Room Reservation Information System At Hotel Mandarin Oriental Jakarta Through Website By On-Line Using PHP and MySQL - Retno Ningrum; Ristyawati Ristyawati., SKom, MMSI (Jurnal Sistem Informasi, 2007)
Website of the Hotel Mandarin Oriental Jakarta is specifically created to provide information of interest to consumers in order to attract their interest and facilitate the prospective guests to make reservations in on - line. Website created contains a link - a link to a page that shows each - each of them about the history of the establishment Hotel Mandarin Oriental Jakarta, display pictures - pictures of rooms, reservation form that can be directly on the content whenever you want to make reservation and tampilah guest book if you want to send a critique and suggestions. This website is also created with the aim admin login view, edit, delete and add data and the data room reservation.